2018
DOI: 10.3389/fphar.2018.00099
|View full text |Cite|
|
Sign up to set email alerts
|

The Association of Unfavorable Traffic Events and Cannabis Usage: A Meta-Analysis

Abstract: Background: In the last years were published many epidemiological articles aiming to link driving under the influence of cannabis (DUIC) with the risk of various unfavorable traffic events (UTEs), with sometimes contradictory results.Aim: The primary objective of this study was to analyze whether there is a significant association between DUIC and UTEs.Materials and Methods: We used two meta-analytical methods to assess the statistical significance of the effect size: random-effects model and inverse variance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 50 publications
(69 reference statements)
1
51
0
6
Order By: Relevance
“…The alternative to deal with these peculiarities related to herbal medicines is the determination of ADMET properties of pure constituents of the formulation, through in vitro tests, for example, Caco-2 cells, human liver microsomes, and cultured human hepatocytes [ 80 ]. In this context, the ADMET properties of the flavonoids iso-orientin, isovitexin, luteolin, apigenin, and kaempferol present in P. incarnata have been described in the literature [ 80 , 83 , 84 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The alternative to deal with these peculiarities related to herbal medicines is the determination of ADMET properties of pure constituents of the formulation, through in vitro tests, for example, Caco-2 cells, human liver microsomes, and cultured human hepatocytes [ 80 ]. In this context, the ADMET properties of the flavonoids iso-orientin, isovitexin, luteolin, apigenin, and kaempferol present in P. incarnata have been described in the literature [ 80 , 83 , 84 ].…”
Section: Methodsmentioning
confidence: 99%
“…Absorption processes are evaluated by blood-brain barrier (BBB) penetration and human intestinal absorption (HIA) methods that demonstrated high absorption through human intestine and side effects on absorption through BBB for iso-orientin, isovitexin, and luteolin. Apigenin and kaempferol showed positive values for both BBB and HIA [ 80 , 83 , 85 ]. The importance of a substance crossing the BBB is partially related to the required biological activity, and this is based on structural and physicochemical characteristics, such as lipophilicity, molecular size, desolvation potential, pKa-to-charge ratio, and hydrogen bond [ 80 , 86 , 87 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bondallaz et al () review this literature and find that marijuana use impairs driving primarily by increasing lane weaving and decreasing the mean distance between vehicles. However, they also find significant discrepancies between studies and note the “the neurobiological mechanisms underlying the effects … remain poorly understood, as does the correlation between body fluids concentrations and psychoactive effects of THC.” Hostiuc et al () performed a meta‐analysis of epidemiological studies of marijuana consumption and driving performance and found a statistically insignificant effect size and substantial bias favoring the publication of studies that showed a positive association between marijuana consumption and traffic accidents.…”
Section: Introductionmentioning
confidence: 99%
“…Illegal cannabis smoked on college campuses in the 1970s had 3-5% THC, whereas legal cannabis sold in Washington State today averages 20% THC (28). Higher potency is concerning because of greater risk of adverse psychiatric effects and greater potential to transition light users into daily users and cannabis use disorders (29)(30)(31). For example, a study in the Netherlands found first-time drug treatment admissions for cannabis rose following increasing cannabis potency (32).…”
Section: Cap the Potency Of Cannabis Productsmentioning
confidence: 99%